Synthesis of Bio lubricant from Bhallataka oil - Dr. Vustelamuri Padmavathi,; Senivarapu Ankit Reddy, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The demand for a renewable and biodegradable lubricant as a substitute for fossil fuel-based lubricant has increased due to strong environmental concerns and expanding regulations over contamination and pollution in the environment. This study investigated the potential of using Semecarpus anacardium L.f. oil, which was identified as a potential raw material for biodiesel, as a feed stock for bio lubricants. Epoxidation and hydrolysis reactions were used to synthesize bio-lubricant. Epoxidized SA L.f oil was made using peroxyformic acid, which was produced on the spot by reacting hydrogen peroxide and formic acid with sulfuric acid acting as a catalyst. The oxirane value of the oil was 3.77, indicating that the unsaturated bonds were almost entirely converted to oxirane, while the iodine value decreased from 90.7 to 2.01 mg I2/g. ESAO
Keywords: Epoxidation; Bhallataka oil; Lubricants; Oxidation Stability